2017
DOI: 10.1080/1028415x.2017.1299437
|View full text |Cite
|
Sign up to set email alerts
|

Holothuria scabraextracts exhibit anti-Parkinson potential inC. elegans: A model for anti-Parkinson testing

Abstract: The study indicated that the H. scabra extracts have anti-Parkinson potential in the C. elegans model. These findings encourage further investigations on using the H. scabra extract, as well as its active constituent compounds, as a possible preventive and/or therapeutic intervention against PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…degeneration of the DA neuron in C. elegans, including foodsensing behavior and the shortened lifespan. These results are consistent with the previous studies that have reported 6-OHDA-induced parkinsonism in both in vitro and in vivo models (Latchoumycandane et al, 2011;Bagga et al, 2015;Chalorak et al, 2018). 6-OHDA selectively induced the toxicity in the DA neurons by entering the cell through dopamine transporter which expressed exclusively in the DA neuronal cell surface (Nass et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…degeneration of the DA neuron in C. elegans, including foodsensing behavior and the shortened lifespan. These results are consistent with the previous studies that have reported 6-OHDA-induced parkinsonism in both in vitro and in vivo models (Latchoumycandane et al, 2011;Bagga et al, 2015;Chalorak et al, 2018). 6-OHDA selectively induced the toxicity in the DA neurons by entering the cell through dopamine transporter which expressed exclusively in the DA neuronal cell surface (Nass et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Whole body-ethyl acetate (WBEA), whole body-butanol (WBBU), and body wall-ethyl acetate (BWEA) ( 27 ) are extracts of sea cucumber Holothuria scabra . These compounds could significantly attenuate the degeneration of DA neurons induced by 6-OHDA in caenorhabditis elegans [68]. Moreover, these extracts could inhibit abnormal aggregation of α-synuclein, and restore lipid content [68].…”
Section: Potential Candidates From Marine-derived Compounds For Thmentioning
confidence: 99%
“…Triterpene glycosides or saponins have been found to be major constituents in the n-butanol fractions that may act in the fat metabolism. [18][19][20] Similarly, a previous study reported that triglyceride accumulation was suppressed and delayed in rats fed with high-fat diet by saponins isolated from the temperate sea cucumber, Cucumaria frondosa. 21 We further found that the effectiveness of both BW and CT extracts in decreasing of fat accumulation and triglyceride levels were similar, which implied that BW and CTs possess similar groups of bioactive saponins.…”
Section: Discussionmentioning
confidence: 83%
“…These results indicated that the bioactive compounds that reduced fat and triglyceride levels were concentrated in the n ‐butanol fraction. Triterpene glycosides or saponins have been found to be major constituents in the n ‐butanol fractions that may act in the fat metabolism . Similarly, a previous study reported that triglyceride accumulation was suppressed and delayed in rats fed with high‐fat diet by saponins isolated from the temperate sea cucumber, Cucumaria frondosa .…”
Section: Discussionmentioning
confidence: 92%